2019
DOI: 10.1186/s12903-019-0989-9
|View full text |Cite
|
Sign up to set email alerts
|

Oral health related quality of life of patients with class III skeletal malocclusion before and after orthognathic surgery

Abstract: BackgroundOrthognathic surgery includes improvement of morphology and function of occlusion as well as psychological perception and oral health-related quality of life (OHRQoL) of patients. The aim of this study was to determine the OHRQoL of patients with class III skeletal malocclusion before and after orthognathic surgery.Materials and methodsA total of 112 skeletal class III patients including 39 (34.8%) males and 73 (65.2%) females participated in this descriptive quasi-experimental study in three groups:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 20 publications
3
28
1
Order By: Relevance
“…The authors found that during the decompensation phase of orthodontic treatment, the patients' quality of life had significantly decreased, whereas after the surgical orthodontic treatment, it had been significantly improved. The same observations presented Rezaei et al [30].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The authors found that during the decompensation phase of orthodontic treatment, the patients' quality of life had significantly decreased, whereas after the surgical orthodontic treatment, it had been significantly improved. The same observations presented Rezaei et al [30].…”
Section: Discussionsupporting
confidence: 80%
“…Unlike, the authors found that there were no statistically significant differences regarding the OHIP-14 values before and after orthodontic treatment. However, most of the authors, who compared the OHIP-14 values before and after orthodontic treatment, found that the patients' quality of life had significantly improved after orthodontic treatment [27][28][29][30]. Moreover, Zheng et al [31] found that the positive impact of orthodontic treatment on the patients' quality of life depends on the type of malocclusion.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, orthognathic surgery alone has already shown excellent results in terms of improving overall patient satisfaction. Aiming to assess oral health-related quality of life before and after orthognathic surgery, Rezaei et al [ 7 ] examined 112 adult patients with class III skeletal malocclusion using the Short Form Oral Health Impact Profile (OHIP-14) and Orthognathic Quality of Life (OQLQ) questionnaires. Their results showed that orthognathic surgery improved the quality of life of these patients, as well as their satisfaction, self-confidence, and oral function.…”
Section: Clinical Discussionmentioning
confidence: 99%
“…The level of patient satisfaction may decrease before surgery due to the lack of knowledge of patients about the phases of orthodontic treatment. Thus, as occurred in the present case, it is up to the multidisciplinary team to raise patient awareness about the therapeutic phases to potentially increase the level of satisfaction with the treatmen [ 7 ].…”
Section: Clinical Discussionmentioning
confidence: 99%
“…21 Previous studies considered a concave profile less attractive and an increase in lower third of the face is to be more attractive than decreased facial height. 21,22 Although women will report a greater negative impact on their quality of life from their malocclusion than men, 23,24 sex is not considered to be a decisive factor since differences were observed only among those who accepted surgery: Females have experienced greater difficulties in social interactions and were more aware of their aesthetics than males. This can be explained with females' higher aesthetic standard as they influence a larger role in females' lives.…”
Section: F I G U R E 1 Comparison Of Dimensions Of Quality Of Life Between Ioftn Grades (Whiskers Represent 95% Confidence Intervals)mentioning
confidence: 99%